A Professional Competency Development Model: Implications for Extension Educators - Nav R. Ghimire; Robert A. Martin (Journal of International Agricultural and Extension Education, 2011)
Professional development refers to continuing education designed to enhance competencies, skills, and knowledge. There is a need for a professional development model based on the educational processes used by educators of adults. A professional competency development model was constructed from a study grounded on four educational process areas in Extension. In this study, 441 randomly selected Extension educators in the North Central Region of the United States participated through an online survey. The proposed model has implications for designing professional competency development programs in the areas of needs assessment/program development, teaching and learning methods, delivery strategies, and evaluation methods. It also indicates the best time and place for Extension educators to develop the competencies and suggests a mechanism to continuously identify the knowledge and skills needed to obtain the best results. This model could be used to develop educational programs in a variety of national and international settings.
Keywords: Extension; Educational processes; Professional development